THE FIRST EXPERIENCE OF LEFT ATRIAL APPENDAGE OCCLUDING DEVICES IMPLANTATION FOR PREVENTION OF STROKE IN THE STATE RESEARCH CENTRE FOR PREVENTIVE MEDICINE - K. V. Davtyan; O. N. Tkacheva; A. A. Kalemberg; S. N. Koretsky (Рациональная фармакотерапия в кардиологии, 2015)
Some aspects of prevention of thromboembolic events in patients with atrial fibrillation, in particular, the use of implantable left atrial appendage occluding devices are discussed. Along with the literature review on this issue, the results of authors own experience of left atrial appendage occluding devices implantation is presented.